Elucidating the Potential of Native Rhizobial Isolates to Improve Biological Nitrogen Fixation and Growth of Common Bean and Soybean in Smallholder Farming Systems of Kenya - Ernest Wandera Ouma; Anne Mercy Asango; John Maingi; Ezekiel Mugendi Njeru (International Journal of Agronomy)
Identification of effective indigenous rhizobia isolates would lead to development of efficient and affordable rhizobia inoculants. These can promote nitrogen fixation in smallholder farming systems of Kenya. To realize this purpose, two experiments were conducted under greenhouse conditions using two common bean cultivars; Mwezi moja (bush type) and Mwitemania (climbing type) along with soybean cultivar SB 8. In the first experiment, the common bean cultivars were treated with rhizobia inoculants including a consortium of native isolates, commercial isolate (CIAT 899), a mixture of native isolates and CIAT 899, and a control with no inoculation. After 30 days, the crop was assessed for nodulation, shoot and root dry weights, and morphological features. In the second experiment, soybean was inoculated with a consortium of native isolates, commercial inoculant (USDA 110), and a mixture of commercial and native isolates. Remarkably, the native isolates significantly (p<0.001) increased nodulation and shoot dry weight across the two common bean varieties compared to the commercial inoculant, CIAT 899. Mixing of the native rhizobia species and commercial inoculant did not show any further increase in nodulation and shoot performance in both crops. Further field studies will ascertain the effectiveness and efficiency of the tested indigenous isolates.